Intergenerational equity : environmental and cultural concerns - Cottier, Thomas; Lalani, Shaheeza; Siziba, Clarence (World Trade Institute advanced studies, 2019)
In Intergenerational Equity: Environmental and Cultural Concerns, the editors have produced an important, broad-based volume on intergenerational equity. The authors explore the principle of intergenerational equity in many dimensions, from the theoretical to the practical. While the primary focus is on intergenerational equity in the context of environmental resources and cultural heritage, the principle is also addressed in a broad array of other contexts. The final section of the volume considers intergenerational justice as it applies to Indigenous peoples, genocide, migration, sovereign wealth funds and foreign investment. The chapters also provide a critical analysis of the issues and a consideration of the difficulties in implementing intergenerational equity.